Trends in Colorectal Cancer Incidence Rates in Saudi Arabia (2001–2016) Using Saudi National Registry: Early- Versus Late-Onset Disease - Alyabsi, Mesnad; Algarni, Mohammed; Alshammari, Kanan (Frontiers in Oncology, 2021)
Early-onset (<50 years old) colorectal cancer (CRC) has been increasing worldwide and is associated with poor outcomes. Over 85% of the Saudi population are < 50 years old, which put them at heightened risk of early-onset CRC. No study assessed the trends in CRC incidence rates among the Saudis. The Joinpoint Regression software by the Surveillance, Epidemiology, and End Results (SEER) program was used to estimate the magnitude and direction of CRC incidence trends by age and gender. The Annual Percentage Change (APC) and the Average Annual Percentage Change (AAPC) between 2001 and 2016 were computed. In a sensitivity analysis, we also assessed trends using various age groups. Between 2001 and 2016, the early-onset CRC incidence (per 105) increased from 1.32 (95% CI: 1.11, 1.54) to 2.02 (95% CI: 1.83, 2.22) with AAPC (2.6, 95% CI: -0.4, 5.7). At same period, the late-onset incidence increased from 3.54 (95% CI: 3.10, 3.97) to 9.14 (95% CI: 8.62, 9.66) with AAPC (6.1, 95%CI: 3.5, 8.8). Among early-onset CRC patients, age 40-49 has the highest rates and women in this age group has higher rate than men. Our national data showed a gradual increase in CRC incidence rates, which reflect the global concern of early-onset CRC. Further research is needed to understand the etiology of early-onset CRC. Primary health care providers must be alerted about the increasing rate of early-onset CRC. To reduce the future burden of the disease, initiating CRC screening before age 50 is warranted.